Novel Antioxidant Packaging Films Based on Poly(ε-Caprolactone) and Almond Skin Extract: Development and Effect on the Oxidative Stability of Fried Almonds - Arantzazu Valdés García; Nerea Juárez Serrano; Ana Beltrán Sanahuja; María Carmen Garrigós (MDPI AG, 2020)
Antioxidant films based on poly(ε-caprolactone) (PCL) containing almond skin extract (ASE) were developed for food packaging applications. The effect of ASE incorporation on the morphological, structural, colour, mechanical, thermal, barrier and antioxidant properties of the prepared films were evaluated. The structural, tensile and thermal properties of the films were not altered due to ASE addition. Although no significant differences were observed for the oxygen permeability of samples, some increase in water absorption and water vapour permeability was observed for active films due to the hydrophilic character of ASE phenolic compounds, suggesting the suitability of this novel packaging for fatty foods conservation. ASE conferred antioxidant properties to PCL films as determined by the DPPH radical scavenging activity. The efficiency of the developed films was evaluated by the real packaging application of fried almonds at different ASE contents (0, 3, 6 wt.%) up to 56 days at 40 °C. The evolution of peroxide and p-anisidine values, hexanal content, fatty acid profile and characteristic spectroscopy bands showed that active films improved fried almonds stability. The results suggested the potential of PCL/ASE films as sustainable and antioxidant food packaging systems to offer protection against lipid oxidation in foods.